The vital role of potassium in the osmotic mechanism of stomata aperture modulation and its link with potassium deficiency - Cochrane, Thomas T (Landes Bioscience, 2009)
Potassium deficiency symptoms of crops are well documented. However, the role of potassium in relation to the osmo-modulation of leaf stomata apertures was only discovered in the early 1970s. Our findings related to the differences between the osmotic properties of KCl and sucrose solutions provided an insight into that mechanism. In this report those findings are re-examined using a minor modification in the way their osmotic properties are calculated. The modification did not result in significant changes to the previous calculations. The properties of the KCl and sucrose solutions were subsequently compared with those of an extended series of inorganic and organic solutes. The calculations re-confirm that the osmotic properties of different solutes vary considerably. Research into the osmotic properties of solutes found in plant tissues may help elucidate other subtle plant physiological mechanisms. The findings highlight the vital role of potassium in plants. Its deficiency probably triggers a signal that results in the flow of potassium from the older leaves to support stomata modulation in the young leaves. This facilitates the survival of the plant, but leads to the necrosis of the older leaves and retarded growth.